Improving Student Learning Outcomes Using the Problem Based Learning Model in Islamic Learning at SMP Negeri 1 Sungai Mas - Mardi; Hastuti (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to test the effectiveness of Problem-Based Learning (PBL) in improving student learning outcomes in Islamic Education at SMP Negeri 1 Sungai Mas. This study used a quasi-experimental design with pretest and posttest assessments, involving 60 students divided into two groups: an experimental group that received PBL instruction and a control group that followed traditional teacher-centered instruction. The pretest and posttest results showed a significant increase in the experimental group's academic performance, indicating that PBL improves students' understanding, retention, and application of the subject matter. The experimental group engaged in problem-solving activities that required collaboration, critical thinking, and practical application of Islamic teachings in real-world contexts. In contrast, the control group received direct instruction through lectures and individual assignments. Data analysis revealed that the experimental group showed higher levels of engagement, critical thinking, and improved academic performance compared to the control group. The findings suggest that PBL promotes deeper learning and greater student participation, making it an effective teaching method in Islamic Education. Based on the results, this study recommends that teachers consider implementing PBL as an alternative to traditional methods, as it not only improves academic outcomes but also encourages active learning, collaboration, and the development of important cognitive skills. This study contributes to the growing body of research supporting active learning strategies in education, highlighting the potential of PBL to improve the quality and effectiveness of teaching and learning in Islamic Education.